Russian Orthodoxy resurgent: faith and power in the new Russia - Garrard, John Gordon (Princeton Univ. Press, 2008)
Prologue: Russian Orthodoxy resurgent / Sergiev Posad -- The end of the Atheist empire -- A new hope -- Rebuilding holy Moscow -- Accursed questions: who is to blame? -- Irreconcilable differences: Orthodoxy and the West -- The Babylonian legacy: exiles, martyrs, and collaborators -- A faith-based army -- Epilogue: twenty years after: from party to patriarch